2016
DOI: 10.3389/fncom.2016.00065
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Single Neuron Extracellular Electric Potentials and Network Local Field Potentials using LFPsim

Abstract: Local Field Potentials (LFPs) are population signals generated by complex spatiotemporal interaction of current sources and dipoles. Mathematical computations of LFPs allow the study of circuit functions and dysfunctions via simulations. This paper introduces LFPsim, a NEURON-based tool for computing population LFP activity and single neuron extracellular potentials. LFPsim was developed to be used on existing cable compartmental neuron and network models. Point source, line source, and RC based filter approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 61 publications
1
62
0
Order By: Relevance
“…We simulated recording of local field potentials (LFPs) in the model. LFP signal was calculated by summing the extracellular potential contributed by each segment of each neuron (see Methods for details) 107 . LFP revealed physiologically-realistic oscillations in delta (0.5-4 Hz) and high beta to low gamma (25-40 Hz) ranges across layers and populations (Figs.…”
Section: Oscillations and Cross-frequency Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…We simulated recording of local field potentials (LFPs) in the model. LFP signal was calculated by summing the extracellular potential contributed by each segment of each neuron (see Methods for details) 107 . LFP revealed physiologically-realistic oscillations in delta (0.5-4 Hz) and high beta to low gamma (25-40 Hz) ranges across layers and populations (Figs.…”
Section: Oscillations and Cross-frequency Couplingmentioning
confidence: 99%
“…The NetPyNE tool also includes the ability to simulate local field potentials (LFPs) obtained from extracellular electrodes located at arbitrary 3D locations within the network. The LFP signal at each electrode is obtained using the "line source approximation" 107,19,77 , which is based on the sum of the membrane current source generated at each cell segment divided by the distance between the segment and the electrode. The calculation assumes that the electric conductivity and permittivity of the extracellular medium are constant everywhere and do not depend on frequency.…”
Section: Model Implementation Simulation and Analysismentioning
confidence: 99%
“…Extracellular potential generated from a granule neuron with dysfunction showed failed and delayed response. LFP reconstructed from the circuit model with dysfunction showed distorted TC waves, attributing ionic currents to the generation of LFP [29,37] and suggest that dysfunction at individual neurons in the network reflected in the population response. The study also revealed the effect of dysfunction at single neuron in population code attributing observations on circuit behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The total LFP was calculated as linear sum of individual node LFPs. On-the-fly implementation of LFP modelling schema effectively reduced the storage space [37] . All LFP traces were averaged traces from 15 simulation runs.…”
Section: Implementation and Lfp Simulationmentioning
confidence: 99%
See 1 more Smart Citation